2004
DOI: 10.1111/j.1540-6261.2004.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Asset Location and Allocation with Taxable and Tax‐Deferred Investing

Abstract: We investigate optimal intertemporal asset allocation and location decisions for investors making taxable and tax-deferred investments. We show a strong preference for holding taxable bonds in the tax-deferred account and equity in the taxable account, ref lecting the higher tax burden on taxable bonds relative to equity. For most investors, the optimal asset location policy is robust to the introduction of tax-exempt bonds and liquidity shocks. Numerical results illustrate optimal portfolio decisions as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(77 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…A family strategy is shown to be accepted for many parameter combinations, especially in families with low marginal tax rates, if the heirs are very wealthy, or in a case where the retiree has an average population life expectancy. Outside the family or annuitization context similar frameworks were recently applied by Michaelides (2003, 2005), Dammon et al (2004), and Cocco et al (2005), as well as Rodepeter and Winter (2005).…”
Section: Introductionmentioning
confidence: 94%
“…A family strategy is shown to be accepted for many parameter combinations, especially in families with low marginal tax rates, if the heirs are very wealthy, or in a case where the retiree has an average population life expectancy. Outside the family or annuitization context similar frameworks were recently applied by Michaelides (2003, 2005), Dammon et al (2004), and Cocco et al (2005), as well as Rodepeter and Winter (2005).…”
Section: Introductionmentioning
confidence: 94%
“…However, older households tend to benefit from maintaining a respectable allocation to equities. For example, using Monte Carlo simulation analysis and reasonable investment return assumptions to determine optimal portfolio allocation, Dammon et al (2004) reported the average overall proportion of equity within a portfolio for households at least 55 years of age is predicted to be no smaller than 53%. Lai (2008) contended that increased appetite for equities among older households is further justified by the desire to protect inflation and mitigate longevity risk (the risk of outliving assets).…”
Section: Allocation To Risky Assetsmentioning
confidence: 99%
“…For example, tax deferral on retirement accounts has been shown to increase the expected return on investment assets (Amromin et al 2007;Engen and Gale 1997), leading to a higher optimal portfolio share in sheltered accounts. This and an increased willingness to invest in equities within these accounts led to riskier portfolios among the more financially sophisticated and risk-averse baby boom cohort (Calvet et al 2009; Center for Retirement Research 2009; Dammon et al 2004;Follain and Melamed 1998).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…As argued in a series of important papers (Dammon, Spatt, and Zhang (2004) and Huang (2008)), tax incentives can tilt the tax-deferred account towards bonds and taxable accounts towards stocks.…”
Section: Economic Mechanisms Of Tax Deferralmentioning
confidence: 99%